Monitoring individual migration in Myanmar: December 2021 - June 2024 - van Asselt, Joanna; Synt, Nang Lun Kham; McCord, Dedrick (International Food Policy Research Institute, 2025)
Drawing on data from seven rounds of the Myanmar Household Welfare Survey (MHWS), conducted between December 2021 and June 2024 with over 12,000 respondents per round, this report examines individual migration, migration in which one or a few household members leave the household. Over the two-and-a-half-year period from December 2021 to June 2024, an estimated 9 million household members aged 15 and older—17 percent of the total population and 28 percent of the adult population—migrated from their households. During this time, the states of Kachin, Kayin, and Mon reported the highest migration rates, with over 35 percent of the adult population migrating.